Clinical, Imaging, and Pathological Suppression of Synovitis in Rheumatoid Arthritis: Is the Disease Curable? - Bugatti, Serena; Sakellariou, Garifallia; Luvaro, Terenzj; Greco, Maria Immacolata; Manzo, Antonio (Frontiers in Medicine, 2018)
The management of patients with rheumatoid arthritis (RA) has witnessed a dramatic revolution in recent years, and disease remission has become an increasingly achievable outcome. Rheumatologists are now facing the urgent question of whether, once remission has been achieved and stably maintained, drugs can be tapered and even discontinued. The concept of disease remission however encompasses progressive layers of complexity, all of which need to be disentangled before considering RA as a ‘curable’ condition. As the synovial membrane represents the ultimate target of the pathological process of RA, a critical issue remains whether disease remission coincides with true suppression of inflammation and definitive tissue ‘healing’. In this short review, we will provide a critical summary of recent data investigating the possibility of controlling RA synovitis at the clinical, imaging or pathological level. Potential advantages and limitations of these perspectives in the definition of remission are also discussed.